Clinicohematological profile of pancytopenia: a study from a tertiary care hospital - Yadav, Rakesh Kumar; Kumar, Sujit (International Journal of Advances in Medicine, 2020)
Background: Pancytopenia is common clinical condition which we encounter in our daily clinical practice. Pancytopenia is characterized by decrease in all the three major components of blood like Red Blood Corpuscles, White blood Corpuscle, and platelets. This study was carried out to look for causes of pancytopenia and clinical presentations at tertiary care hospital in north India. Methods: The study was conducted at MLN Medical College, Allahabad in the Department of Medicine between June 2018 to July 2019. Total 125 patients who attended department of medicine were screened for study. After exclusion 94 patients were studied prospectively. Results: Out of 94 patients 59 were males, and 35 females in the study group. Male to female ratio was 1.6:1. Maximum patients were between 20 years to 35years of age group. Pallor and weakness were most common clinical feature in this study group. Out of various etiological causes vitamin B12 deficiency was the commonest in our study. 48(51%) patients had megaloblastic anemia due to vitamin B12 deficiency. Second most common etiological factor was hypo plastic/aplastic anemia. Other etiological abnormalities were hypersplenism, dengue, malaria, sepsis, myelodysplastic syndrome and multiple myeloma. Conclusions: Bone marrow examinations, aspiration cytology or biopsy are important tool for diagnosis of pancytopenia. Underlying cause and severity of disease determine the outcome of pancytopenia. The present study concluded that most of patients with pancytopenia have treatable cause so early diagnosis will be helpful for management of patients.